No association between ZNF804A rs1344706 and schizophrenia in a case-control study of Han Chinese. (8th April 2016) - Wang, Jun; Zhao, Shuidi; Shugart, Yin Yao; Zhou, Zhenhe; Jin, Chunhui; Yuan, Jianmin; Wang, Guoqiang; Wang, Dong; Cheng, Zaohuo; Zhang, Fuquan
Highlights: ZNF804A rs1344706 is a promising risk variant for schizophrenia in European populations. We analyzed the association of rs1344706 with schizophrenia in Han Chinese, including 1284 cases and 990 healthy controls. We did not detect a significant association of rs1344706 with schizophrenia. Abstract: Previous studies indicated that the single nucleotide polymorphism (SNP) rs1344706 within the gene ZNF804A was a promising risk variant for schizophrenia in European populations. However, existing results are inconsistent in Han Chinese. Hoping to validate the association of rs1344706 with schizophrenia susceptibility in Han Chinese, we conducted a case-control study in 1284 cases and 990 healthy controls from Jiangsu Province, China. We did not detect any significant between-group difference (all P > 0.05) in either allele or genotype frequency under any genetic model between cases and controls. Stratified analysis by sex also failed to find any significant association. Our results did not support the association of rs1344706 with schizophrenia in Han Chinese, and further association studies with large samples from other ethnic backgrounds and focus on more SNPs of ZNF804A are warranted.